Gender Equality: A Case Study of Janaki Sooriyarachichi’s Picture Book The Flying Train - Mehdi Ghasemi (Hrvatska udruga istraživača dječje književnosti (HIDK) / Croatian Association of Researchers in Children’s Literature (CARCL), 2022)
Gender inequality is one of the most important concerns of the world today, even in children’s story books. The creation of “biased” or “unbiased” story books which blur or highlight gender differences help to form gender equality or inequality right from early childhood. Through a thorough examination of The Flying Train (2003), a story written in English for children between six and ten years of age, this paper intends to explain how Janaki Sooriyarachchi – the writer and illustrator of the story – attempts to validate both feminine and masculine voices and visions and balance gender issues both in the text and in the illustrations of the analysed narrative.